Like a Fly against a Pane of Glass: Simone Weil in the Context of Contemporary Theories of Suffering - Düringer , Eva-Maria (Labyrinth, 2023)
The last five years have seen a welcome rise in philosophical research on suffering. In this paper I will introduce the main new proposals and point out their respective weak-nesses. All accounts focus on an important aspect of suffering, but each one is too nar-row. I will sketch an account of suffering as being forced to endure the unendurable, based on Simone Weil's writings. I will argue that not only does this account manage to encompass the important aspects of suffering emphasised by current research, but that it much more plausibly brings out the ethical dangers, such as seeking consolations in fabricated narratives of meaning, and the value of suffering, such as enabling the mind to make unfiltered contact with reality.